Arterial hypertension - Genetics - Quiroga de Michelena, María Isabel (2010)
Regulation of blood pressure depends on complex mechanisms that include multiple genetic and epigenetic variations. There is a delicate balance between genetic, epigenetic and environmental factors that, when disrupted, lead to hypertension. In most cases blood hypertension is primary or essential, and rarely is inherited through mutation of a single gene. This review will focus on genes involved in multifactorial blood hypertension and in the rare cases of monogenic hypertension. The pharmacogenomic advances and perspectives in the era of genomic medicine will also be reviewed.